Healthcare spending and utilization for pediatric Irritable Bowel Syndrome in a commercially insured population. Issue 11 (5th April 2021) - Beinvogl, Beate; Palmer, Nathan; Kohane, Isaac; Nurko, Samuel
Abstract: Background: Pediatric Irritable Bowel Syndrome (IBS) is common and can be associated with disabling gastrointestinal symptoms. Comprehensive data regarding utilization and cost of pediatric IBS are lacking. Our aim was to determine the annual all‐cause spending and healthcare utilization in pediatric IBS. Methods: Cross‐sectional cohort study using a national claims database of commercially insured individuals. 932, 592 members, age 8–18 years, were included. Members were selected based on PheWas codes and continuous enrollment in 2014. Linear and binomial regression models were used to calculate healthcare spending and compare comorbidities between IBS subjects and controls. Key Results: 1215 members with claims for IBS (68.4% female) and 931, 377 controls (55.7% female) were included. Mean age was 15.03 ± 2.83 (median 16) years in the IBS group and 13.14 ± 3.12 (median 13) years in controls. Mental health and chronic pain comorbidities were more prevalent in the IBS cohort. Healthcare spending : The mean annual all‐cause incremental spending of members with IBS was $6, 364.60 compared to controls when adjusting for age and gender. Healthcare utilization : Members with IBS had increased healthcare utilization including higher rates of inpatient, outpatient, and emergency room visits, and higher rates of health service utilization including medical care, radiology/laboratory services, surgery, anesthesia, mental health, and physical therapy. General pediatrics was more frequently consulted by controls. All subspecialty consultations, with the exception of dental medicine and endocrinology, were sought more frequently by IBS patients. Conclusion: Patients with IBS incur significant annual spending through increased healthcare utilization. Abstract : National claims data shows that children and adolescents with Irritable Bowel Syndrome incur significant annual spending ($6, 364.60 compared to controls when adjusting for age and gender) through increased health care utilization.